Mechanical Tolerance Stackup and Analysis. - Fischer, Bryan R. (Dekker Mechanical Engineering., 2011)
Use Tolerance Analysis Techniques to Avoid Design, Quality, and Manufacturing Problems Before They Happen Often overlooked and misunderstood, tolerance analysis is a critical part of improving products and their design processes. Because all manufactured products are subject to variation, it is crucial that designers predict and understand how these changes can affect form, fit, and function of parts and assemblies--and then communicate their findings effectively. Written by one of the developers of ASME Y14.5 and other geometric dimension and tolerancing (GD & T) standards, Mechanical Tolerance.